Impact of Prosopis cineraria on Soil organic carbon: Implication for arid agroforestry with a case study of Sardarshahar, Rajasthan - Pareek, Laxmi; Yadav, Vinod Kumar; Tripathi, Suman Lata; Yadav, Shilpa (International Journal of Environment, Agriculture and Biotechnology, 2024)
Prosopis cineraria (P. cineraria), commonly known as Khejri, plays a significant role in enhancing soil health, particularly in arid and semi-arid regions. This study investigates the impact of Prosopis cineraria on soil organic carbon (SOC) levels in the context of agroforestry systems in Sardarshahar, Rajasthan. The analysis reveals that the presence of this species positively influences SOC concentrations, contributing to improved soil fertility and structure. The deep root system and high biomass production of P. cineraria facilitate the accumulation of organic matter in the soil, leading to higher carbon sequestration potential compared to non-forested areas. Additionally, the integration of this species into arid agroforestry systems can support sustainable agricultural practices in these challenging environments. This case study highlights the ecological benefits of P. cineraria in maintaining soil health in arid regions and discusses about the dynamics of SOC along seasons and soil depth. The findings advocate the importance of incorporating native tree species like Prosopis cineraria into agroforestry practices to enhance soil organic carbon stocks and promote sustainable land management in Rajasthan and similar arid landscapes.